PERAN STRATEGIS KESENIAN NUSANTARA DALAM PETA JALAN INDONESIA EMAS 2045 - Salim, Muhammad Nur; Isma'il, Harun (Paradigma: Jurnal Kajian Budaya, 2026)
The Indonesia Emas (Golden Indonesia) 2045 vision, which targets Indonesia's transformation into a developed nation, tends in practice to prioritize material development (economy, technology) at the risk of neglecting the nation's character-building. This article argues that the arts of the archipelago must be positioned as a strategic driver to address this gap. Using a literature study method and the conceptual frameworks of Soft Power and Creative Economy, this paper proposes a Cultural Roadmap based on three fundamental pillars. The first pillar is the Revitalization of Arts-Based Education to shape superior human resources with strong character and creativity. The second is the Downstreaming of the Creative Economy to build an authentic and competitive culture-based economic independence. The third is Global Cultural Diplomacy to project the nation's positive influence and image on the international stage. The analysis concludes that these three pillars must be implemented not as separate programs, but as an integrated policy ecosystem where creative human resources fuel economic innovation, and these creative products become the ammunition for effective diplomacy. Integrating this ecosystem into the heart of national planning is a necessity to realize a Golden Indonesia 2045 that is not only materially wealthy but also civilized and noble.